2008
DOI: 10.1177/1073191107306140
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Validity and Measurement Invariance of the 20-Item Toronto Alexithymia Scale in Clinical and Nonclinical Samples

Abstract: The most widely used instrument to measure alexithymia is the 20-item Toronto Alexithymia Scale (TAS-20). However, different factor structures have been found in different languages. This study tests six published factor models and metric invariance across clinical and nonclinical samples. It also investigated whether there is a method effect of the negatively keyed items. Second-order models with alexithymia as a higher order factor are tested. Confirmatory factor analyses showed that the original factor mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
91
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 34 publications
14
91
1
2
Order By: Relevance
“…We therefore agree with Meganck and colleagues (in press) that, bearing in mind the difficulties addressed with self-report scales like the TAS-20 for the measurement of alexithymia, the TAS-20 should not be relied upon alone and should be combined with other alexithymia measures (e.g. Leising et al, 2009;Meganck et al, 2008). …”
Section: Alexithymia and Internal Interpersonal Representationsmentioning
confidence: 62%
“…We therefore agree with Meganck and colleagues (in press) that, bearing in mind the difficulties addressed with self-report scales like the TAS-20 for the measurement of alexithymia, the TAS-20 should not be relied upon alone and should be combined with other alexithymia measures (e.g. Leising et al, 2009;Meganck et al, 2008). …”
Section: Alexithymia and Internal Interpersonal Representationsmentioning
confidence: 62%
“…Similar or even higher magnitude correlations between the TAS-20 EOT factor scale and the TSIA and its domain and facet scales were reported in the validation studies with Canadian and German clinical samples and with the Italian mixed clinical and nonclinical sam-ple (Bagby et al, 2006;Caretti et al, 2011;Grabe et al, 2009). Given the excellent internal consistency of the EOT facet scale of the TSIA, this may be a much better measure of the externally oriented thinking facet of the alexithymia construct than the EOT factor scale of the TAS-20, which has also demonstrated low internal consistency in many other studies (e.g., Kooiman et al, 2002;Meganck et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…The Dutch version of the TAS-20 was developed using a translation and back-translation procedure (Kooiman, Spinhoven, & Trijsburg, 2002); its psychometric properties were found to be adequate in clinical and nonclinical samples (Kooiman et al, 2002;Meganck, Vanheule, & Desmet, 2008). For example, Meganck et al (2008) replicated the three-factor structure and reported internal reliability coefficients that exceeded .70 for the total TAS-20 and the DIF and DDF factors in both student and psychiatric outpatient samples; however, as with several other translations of the TAS-20 (Taylor et al, 2003), Cronbach alpha coefficients were rather low for the EOT factor (.56 in the psychiatric sample and .53 in the student sample). Kooiman et al (2002) demonstrated that the TAS-20 discriminates well between psychiatric patients and adult non-patients, and has excellent three month retest reliability (r = .74).…”
Section: Instrumentsmentioning
confidence: 99%
“…Bagby, one of the original authors of the instrument (Kooiman, Spinhoven, & Trijsburg, 2002). Psychometric qualities of the Dutch version of the TAS-20 were studied in a large clinical and nonclinical sample and can be considered adequate (Meganck et al, 2008).…”
Section: The 20-item Toronto Alexithymia Scalementioning
confidence: 99%
“…Nowadays the most widely used instrument in alexithymia research is the self-report 20-item Toronto Alexithymia Scale (TAS-20;. The psychometric properties of this scale (reliability and factorial validity) have been investigated extensively and are considered adequate (Taylor, Bagby, & Parker, 2003; see also Meganck, Vanheule, & Desmet, 2008). However, the TAS-20 has been criticised due to the inherent difficulty in asking someone to judge a process s/he may not be capable of (Lane, Ahern, Schwartz, & Kaszniak, 1997;Waller & Scheidt, 2004); the sensitivity of the TAS-20 for negative affectivity (Lumley, 2000); and the absence of items reflecting the reduced fantasy dimension of alexithymia.…”
Section: Introductionmentioning
confidence: 99%